SADI-S with Extended Duodeno-Bulb Preservation: Case Report - Ramos Mussa Dib, V (2023)
Obesity has been growing in Brazil and in the world. It is reaching epidemic proportions, and bariatric surgery is the most effective treatment for patients with this disease. Among the procedures described in the literature, ileal surgeries such as biliopancreatic diversion with duodenal switch (BPD-DS) and single-anastomosis duodeno-ileal bypass with sleeve gastrectomy (SADI-S) present better long-term results in terms of weight loss and comorbidities control. However, there are concerns regarding long term nutritional problems with these procedures. In this case report the aim is to demonstrate the technical feasibility of preserving an extended duodenal bulb segment, in the SADIS-S procedure, when there are difficulties in dissecting the retrobulbar region, as occurred here, due to fibrosis in this area. This assures the maintenance of the proposed surgical technique, in such a situation. The dissection and transection of the duodenum was done 7 cm distally to the pylorus, under endoscopic view, proximally to the papillae, where the tissue was normal. Additionally, due the importance of the duodenal mucosa on minerals and trace elements absorption and the release of important hormones in this region, this case report elicits the evaluation of the impact of this technical modification, which occurred casually, in the nutritional, hormonal and metabolic results, long term. In this case report, the extended duodenal length has demonstrated reasonable weight loss, adequate comorbidities control and good nutritional status, so far. These aspects must be evaluated in the long term, by clinical trials.